2020
DOI: 10.1007/s00170-020-05716-w
|View full text |Cite
|
Sign up to set email alerts
|

A high-precision laser method for directly and quickly measuring 21 geometric motion errors of three linear axes of computer numerical control machine tools

Abstract: Error compensation has become an important means of improving the manufacturing and processing accuracy of computer numerical control (CNC) machine tools. Quick and precise measurement of the various geometric motion errors (GMEs) of CNC machine tools is crucial. We propose a novel laser method for the efficient and direct high-precision measurement of the 21 GMEs of a three-axis CNC machine tool, or three linear axes of a five-axis tool. A corresponding system was developed, comprising a fiber-coupled laser u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…To improve the adaptability of measurement system and model, the same method was used to establish comprehensive measurement models for other types of CNC machine tools. The analysis showed that there are two different measurement modes in the measurement process because of the different types of machine tools [33]. In general, the default measurement mode occurs when the target unit moves with the work table.…”
Section: Matrix When Performing the Y-axis Measurement Htm Ymentioning
confidence: 99%
See 1 more Smart Citation
“…To improve the adaptability of measurement system and model, the same method was used to establish comprehensive measurement models for other types of CNC machine tools. The analysis showed that there are two different measurement modes in the measurement process because of the different types of machine tools [33]. In general, the default measurement mode occurs when the target unit moves with the work table.…”
Section: Matrix When Performing the Y-axis Measurement Htm Ymentioning
confidence: 99%
“…To achieve quick and accurate measurement of the geometric errors of the linear axes of CNC machine tools, our research team proposed a series of measurement systems to direct measure simultaneously the 6DOF geometric error of a single linear axis [29][30][31][32]. A novel method for automatically measuring 21 geometric errors of the three linear axes of CNC machine tools with one-step installation was proposed, and a corresponding measurement system was developed [33,34]. Furthermore, the differences between the two measurement modes were analyzed [35].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of these methods is that the results obtained generally do not include unnecessary error factors such as repeated installation and positioning errors of the measuring device. Feng et al [28][29][30] proposed methods for directly measuring multi-degree of freedom (DOF) geometric errors based on the principle of laser measurement, and the measurement efficiency of the new method is higher than that of conventional laser interferometer measurement. However, many equipment and lenses must be installed when using this method.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, Liu et al have succeeded in measuring the 6-DOF geometric motion errors of a long linear stage simultaneously by combining the geometrical optics method and laser interferometer method 11 . Zheng F et al use two CCRs and one beam splitter (BS) to comprise a six-error sensing component and propose a direct method for simultaneously measuring six geometric motion errors (GMEs) of a single linear axis, and finally, realize the measurement of 21 GMEs of three linear axes of a machine tool 12 . These systems are implemented on mechanical platforms that require high precision displacement stages.…”
Section: Introductionmentioning
confidence: 99%